Analisis Dan Pemodelan Proses Bisnis Menggunakan Business Process Improvement (BPI) Pada Lembaga Bimbingan Belajar (Studi Kasus: Lembaga Bimbingan Belajar Prisma) - Arofian Taufi Helmi; Ismiarta Aknuranda; Mochamad Chandra Saputra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
An organization or agency certainly have business processes that are run to support the operational activities of the organizations or agencies in order to achieve the vision and mission have been determined An organization or agency certainly have business processes that are run to support the operational activities of the organizations or agencies in order to achieve the vision and mission have been determined. Prisma learning guidance is one of the learning guidance that is currently growing. Along with the development of a business then the level of service to customers should also be better. Currently in running the business process, LBB Prisma has not had a standard business process. Recording of data is still done manually. The risk of loss of data will increase. Expectation from the chairman of LBB Prima that business processes can run effectively and efficiently. The purpose of this research is to 1) Modeling and simulating business processes on Prisma Student Guidance using BPMN 2) Modeling and simulating recommendations business process using the BPI approach on the Prisma Student Guidance 3) Compare the current business process model and the proposed business process.Research begins with literature studies and data collection through interviews. Next is modeling and simulating current business processes using BPMN, problem analysis, business process improvement analysis using BPI approach, modeling and simulation of proposed business processes and comparison of process simulation results. The results obtained from this research that is 1) Modeling of four business processes that will be improved 2) model Proposed business process using BPI techniques 3) Comparison of current business process simulation results and proposals..